Ethical dilemmas in providing acute medical care at home for children: a survey of health professionals - Penelope A Bryant (BMJ Paediatrics Open)
Objective Acute care at home is increasing. We aimed to determine the views of healthcare professionals on the ethics of providing home care and compare the impact of situational changes on their opinions.Design An analysis of opinions of home healthcare professionals.Setting The Australasian Hospital-in-the-Home Annual Conference, November 2017.Participants Eighty physicians, nurses and allied health staff who provide acute care for children and adults at home.Methods Clinical scenarios were presented about a 14 years old receiving intravenous antibiotics at home via an established home care pathway, and participants were asked to vote manually on whether providing home care was ethical.Main outcomes The proportions of healthcare professionals who believed that provision of home care was ethical in different situations.Results For each question the response rate ranged from 71% to 100%. While the provision of acute home care was deemed ethical by the majority (77/80, 96%), this decreased when other factors were involved such as domestic violence (37/63 (59%) OR 0.06, 95% CI 0.02 to 0.20, p<0.001) and parental reluctance (28/67 (42%) OR 0.02, 95% CI 0.008 to 0.09, p<0.001). The age of consent affected the proportion who considered home care ethical against parental wishes: 16 years (48/58, 83%) versus 14 years (33/53, 52%) OR 4.4, 95% CI 1.9 to 10.1, p<0.001. The lowest proportion to consider home care ethical (16%) was when home care was deemed less than hospital care.Conclusions Home healthcare providers are supportive of the ethics of providing acute care at home for children, although differ among themselves with situational complexities. Applying the tenets of medical ethics (autonomy, non-maleficence, beneficence and justice) can provide insights into the factors that may influence opinions.